Effectiveness of Electrobase Applications in Increasing Understanding of Electronics Concepts - Dolo, Fransiskus Xaverius; Gelu, Afrianus (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This research is a type of development research where the researcher aims to develop an Android-based application specifically designed to help students understand electronics concepts. This application aims to overcome the problems often faced by students in studying electronics material. The application developed has several main features designed to provide solutions to student learning problems. First, this application will provide a complete and structured basic theory of electronics concepts. Based on the results of the research and discussion, it can be concluded that there is a significant effect of the use of the Elektrobase Application and conventional multimedia on students' understanding of concepts in the third semester. This is shown by comparing the scores, where the experimental class had a higher average score than the control class. Also, in the second result from Table 7, the large Sig (2-tailed) value is 0.018, which is less than 0.05. Based on the hypothesis criteria, we reject H0 and accept H1. So, it can be concluded that there is a difference in the average understanding of concepts between the experimental and control classes. From the results in Tables 6 and 7, it can be assumed that the Elektrobase Application is more effective in helping students understand concepts compared to traditional multimedia.